Does the Body Adipose Index (BAI) Work for Elite Athletes? A Comparison of Body Composition Tests Between the Body Adipose Index (BAI) and Bodpod of Female, College Volleyball Players - Marian H. Wooten; Danny Davis; Tommy Thompson; Whitney Jackson (European Scientific Journal, ESJ, 2017)
The Body Adipose Index (BAI) is a relatively new equation used to assess an individual’s percentage of bodyfat. Two benefits of the BAI are ease and low cost of testing. While research has looked at the BAI for a general population sample, the BAI has not been tested on elite athletes. This limited study compared results of BAI testing with results from the BodPod, a wellestablished and precise body composition analysis device, to find out how well the BAI could measure level of bodyfat in female, collegiate volleyball players. Because the volleyball players had higher fat levels that was assumed when selecting a sample population, findings indicated that the BAI appears to work well on a general female population; however, further research is needed to see if this holds true for a larger sample and whether or not the BAI can measure bodyfat accurately for elite athletes.